Study of the Binding of Cuminaldehyde with Bovine Serum Albumin by Spectroscopic and Molecular Modeling Methods - Ali, Mohd Sajid; Rehman, Md Tabish; Al-Lohedan, Hamad A.; Alajmi, Mohamed F. (Journal of Spectroscopy, 2023)
Here, we investigated the interaction of cuminaldehyde with a model carrier protein, bovine serum albumin (BSA). The formation of the BSA–cuminaldehyde complex was confirmed through ultraviolet–visible (UV–Vis) spectroscopy and further proven by detailed intrinsic fluorescence spectroscopic measurements. As observed, cuminaldehyde quenched the intrinsic tryptophanyl fluorescence of BSA. The fluorescence data, before the analyses, were corrected for the inner filter effect (IFE) because of the significant absorption of cuminaldehyde at the excitation wavelength that was employed in the measurements. The typical Stern–Volmer plots were slightly nonlinear; they exhibited negative deviation toward the x-axis, a typical phenomenon that is observed with proteins possessing more than one tryptophan residue. Thus, the modified Stern–Volmer equation was employed to analyze the data. The analyzed data revealed that the interaction of cuminaldehyde with BSA proceeded via a static quenching mechanism and that there was a fair 1 : 1 binding between them. The interaction was strengthened by hydrophobic forces and hydrogen bonding. A lowered concentration of cuminaldehyde did not affect the secondary structure of BSA, although an increased one partially exposed the protein by decreasing its α-helical contents. The molecular dockings and simulations of BSA and cuminaldehyde further confirmed the formation of the stable BSA–cuminaldehyde complex. The in silico results also revealed that the contributions of the hydrophobic interaction and hydrogen bonding were the driving forces that imparted the stability.